Estimates in the Rényi theorem for differently distributed terms - Suhakova, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We obtain estimates for the rate of convergence of the distribution function of a sum of a geometric number of differently distributed random variables to a function of a special kind in the case where the parameter of the geometric distribution tends to zero. We also consider the problem of convergence of inhomogeneous thinning flows, which is closely related to the geometric summation.